The Correlation between Learner Autonomy and English Competence of 8th Graders at a State Junior High School in Surabaya: English - Violla Eka Fernanda; Ahmad Munir (Prodi Tadris Bahasa Inggris, 2023)
This research aimed to investigate the connection between learner autonomy and English competence among 8th-grade students. A correlational design was employed using questionnaire surveys and students' scores in midterm and final examination. The study involved 75 students from a state junior high school in Surabaya. The questionnaire assessed learners' autonomy behaviors, goal-setting skills, and willingness to take responsibility for their language learning, while English competence was measured using students' report scores book. The findings indicated that the 8th graders exhibited a high level of learner autonomy, showing self-directed learning behaviors and taking individual responsibility for their language learning. Furthermore, there was a significant positive correlation between learner autonomy and English competence suggesting that students with greater autonomy tended to demonstrate higher English competence. These results highlight the importance of nurturing learner autonomy to improve English competence. Educators and policymakers can use these findings to develop strategies and interventions that promote learner autonomy and enhance English language learning outcomes. Further research is recommended to explore other factors influencing learner autonomy and its relationship with English competence. Qualitative studies could provide deeper insights into students' perceptions and experiences regarding learner autonomy and its impact on their language-learning journey.